Global Eras and Language Diversity in Indonesia: Transdisciplinary Projects Towards Language Maintenance and Revitalization - Collins, James T (UI Scholars Hub, 2019)
Indonesia is immensely proud of its hundreds of regional languages. This amazing diversity occurs because of the social impact in the three global eras: ancient migration from Asian continent, trading intensification and colonial oppression five hundred years ago, and demographical and communication change in the 21st century. However, now we are witnessing the number decrease of the languages in Indonesia. The resistance and preservation of the inherited languages, which are local languages, in the Indonesian archipelago (Nusantara) language network that is indeed complex must be considered as important components in the Indonesia’s national identity. Along with the accelerated loss of the inherited languages, we are also dealing with the ecological crisis happening in Indonesia. In the 19th century linguistics developed in connection with the progress of biology. Hence, in the 21st century, the handling and studies of languages that are endangered are reasonably related to the contemporary focus on the global ecology studies. Nettle (1999) asserted that the world regions with the high biological diversity are also the regions with the high language diversity. Any research on Nusantara’s flora and fauna should be correlated with the study of endangered languages and dialects. In this paper, we review transdisciplinary planning which is capable of producing understanding and comprehension on the ecological system and regional language community as well as the perspective on the role of the knowledge in order for the academicians and members of the community to make more joint efforts to maintain the ecological system and the Nusantara language network.